Sąd Najwyższy USA w amerykańskim porządku ustrojowo-politycznym - Machaj, Łukasz (L'vìvs'kij nacìnal'nij unìversitet ìmenì Ìvana Franka, 2013)
The Supreme Court of the United States plays a very important role in the American political-and-legal system. It performs a crucial function of constitutional interpretation and adjudication which has been its task since the famous decision in Marbury v. Madison. This duty and right is generally recognized by all political and legal actors. It can be said that in the United States the Constitution is what the Supreme Court says it is. Nevertheless the specific execution of this right by Justices is often criticized, and the accusation of «judicial activism» is often leveled both against the Court in general and against particular judges. It appears, however, that this critique is of a primarily political nature. In conclusion, it can be said that the systemic position of the Supreme Court is best explained by legal realists and functionalists who distinguish between «law in books» and «law in action».
Keywords: Supreme Court of the United States; American political system; American legal system